Coconut fatty acid distillate as novel feedstock for biodiesel production and its characterization as a fuel for diesel engine. (February 2021) - Rajesh, K.; Natarajan, M.P.; Devan, P.K.; Ponnuvel, S.
Abstract: The coconut fatty acid distillate (CFAD) was used as a novel feedstock for biodiesel production in this investigation. Its characterization as fuel in diesel engine was also studied. A maximum biodiesel yield of 92.6% was obtained, when esterification is performed with 10:1 methanol to oil ratio, 2.5% sulphuric acid at 60 °C for 90 min. This is followed by transesterification with optimized parameters of methanol to oil ratio 8:1, 1.5% potassium hydroxide at 60 °C for 90 min. 20%, 40%, 60% and 100% of CFAD biodiesel (CFAB) was added to diesel to form blends CFAB20, CFAB40, CFAB60 and CFAB100. Engine test results showed that the performance of CFAB20 is closer to diesel than the other CFAB blends. The brake thermal efficiency (BTE) of CFAB20 was found to be 4.7% lesser than diesel. Nitrogen oxide emission is higher for all biodiesel blends due to enhanced combustion characteristics. However, carbon monoxide, hydrocarbon and smoke were reduced by 50%, 36.6% and 42.9% respectively for CFAB100 when compared to diesel at full load. Thus it is inferred that the CFAD is a potential source for biodiesel production. CFAB20 can be used in diesel engines with acceptable BTE and reduced emissions without any engine modification. Highlights: A by-product from vegetable oil refinery as feedstock for biodiesel production. The Oil characterization revealed the presence of 91.53% saturated fatty acids. Two-stage transesterification was used due to the high acid value of the oil. Performance and emission results of B20 blend is closer to diesel. CO, HC and smoke opacity of B100 was reduced by 50%, 36.6% and 42.9% at full load.